A multicellular organism with embedded cell clusters from the Ediacaran Weng'an biota (Doushantuo Formation, South China). Issue 5 (10th November 2016) - Cunningham, John A.; Vargas, Kelly; Marone, Federica; Bengtson, Stefan; Donoghue, Philip C. J.
SUMMARY: Three‐dimensional analyses of the early Ediacaran microfossils from the Weng'an biota (Doushantuo Formation) have focused predominantly on multicellular forms that have been interpreted as embryos, and yet they have defied phylogenetic interpretation principally because of absence of evidence from other stages in their life cycle. It is therefore unfortunate that the affinities of the various other Doushantuo microfossils have been neglected. A new conical fossil that is preserved at a cellular level is described here. The fossil contains distinct cell clusters that are characterized and analysed in three dimensions. These clusters are often exposed at the specimen surface, and the fossil preserves many hemispherical craters that are interpreted as positions where clusters have left the organism. The cell clusters may be either reproductive propagules or infesting organisms. Similar clusters are found in a variety of Doushantuo organisms including putative animal embryos and algae.